PHYTOCHEMICAL STUDIES AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF SARCOSTEMMA BREVISTIGMA, WIGHT & ARN. - SM, Dhivya; K, Kalaichelvi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To explore the phytochemical constituents present in Sarcostemma brevistigma using gas chromatography-mass spectrometry (GC-MS). Methods: Preliminary phytochemical analysis of secondary metabolites was made by following standard procedures. GC-MS analysis of the plant extracts was performed by using GC-MS equipped with a DB-35MS capillary standard non-polar column and gas chromatograph interfaced to a Mass Selective Detector (MS-DSQ-II) with Xcalibur software. Results: The qualitative phytochemical analysis of this species exhibited the presence of alkaloids, glycosides, flavonoids, phenols, steroids, amino acids, tannins, terpenoids, quinones, and coumarin. The GC-MS analysis revealed the presence of 24 compounds in the ethanolic extract of aerial part of Sarcostemma brevistigma. The most prevailing compound was 14,17 bis(dimethylaminoamino)[3.3]paracyclophan-5,8-diacetonitrile (14.86%). Conclusion: The study concludes that the species Sarcostemma brevistigma is a potential source for bioactive compounds such as esters, alkanes, alcohols, alkenes, amide, amine, phenol, ketone, and so forth. This study justifies the traditional usage of this species. Keywords: Gas chromatography-mass spectrometry, Sarcostemma brevistigma, Phytochemical compounds, Medicinal plants.